2018
DOI: 10.1002/adem.201800900
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Sr/Mg‐Doped Hardystonite Bioceramics from Preceramic Polymers and Reactive Fillers: Direct Foaming and Direct Ink Writing

Abstract: Novel hardystonite-based bioceramics are obtained by thermal treatment, in air, of silicone resins and reactive fillers. Using commercial silicones embedding SrO and MgO precursors, in addition to CaO and ZnO precursors, a quite complex solid solution (Ca 1.4 Sr 0.6 Zn 0.85 Mg 0.15 Si 2 O 7 ) can be achieved, at 1100 C, instead of pure hardystonite (Ca 2 ZnSi 2 O 7 ), with improvements in biocompatibility and bioactivity. Highly porous foams are obtained by gas evolution at the early stage of heat treatment (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…An interesting approach to generating an analogue of pure hardystonite (Ca 2 ZnSi 2 O 7 ) materials involves the use of preceramic polymers such as polysiloxane and inorganic fillers such as SrCO 3 , and Mg(OH) 2 to produce Sr/Mg doped hardystonite foam materials (Ca 1.4 Sr 0.6 Zn 0.85 Mg 0.15 Si 2 O 7 ) that may be useful as scaffolds for bone tissue engineering 83 . Hybrid treatments combining direct foaming and direct ink writing of silicone‐based pastes have been applied to produce highly porous cellular Sr/Mg doped hardystonite materials after firing at 1,100°C for 1 hr.…”
Section: Biological Evaluations For Specific Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting approach to generating an analogue of pure hardystonite (Ca 2 ZnSi 2 O 7 ) materials involves the use of preceramic polymers such as polysiloxane and inorganic fillers such as SrCO 3 , and Mg(OH) 2 to produce Sr/Mg doped hardystonite foam materials (Ca 1.4 Sr 0.6 Zn 0.85 Mg 0.15 Si 2 O 7 ) that may be useful as scaffolds for bone tissue engineering 83 . Hybrid treatments combining direct foaming and direct ink writing of silicone‐based pastes have been applied to produce highly porous cellular Sr/Mg doped hardystonite materials after firing at 1,100°C for 1 hr.…”
Section: Biological Evaluations For Specific Applicationsmentioning
confidence: 99%
“…MTT assay of fibroblast cells cultured on control condition (tcp), pure hardystonite and Sr/Mg‐doped hardystonite ceramics. The column charts are related to the cell proliferation rate as a function of seeding time at 1, 3, 7, and 14 days 83 . Reproduced with permission from John Wiley & Sons…”
Section: Biological Evaluations For Specific Applicationsmentioning
confidence: 99%
“…Nevertheless, cell differentiation was superior on strontium-substituted hardystonite coatings compared to all the other groups. As both silica-based coatings had similar surface topography, it was suggested that the release of Sr ions—rather than surface topography—was responsible of the higher differentiation on strontium-substituted hardystonite compared to hardystonite ones [140,187,188].…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…To ensure the retention of the component shape after printing, the ink instantly has to be dried, [49] gelled, [50,51] or exposed to a significant viscosity increase [52] based on shear-thinning behavior. In the last decades, progress was made especially in the fields of bioceramics and [53][54][55] functional ceramics, [49,52] among others. Based on this technique, the manufacturing of complex geometries at very high resolution can be achieved.…”
Section: Introductionmentioning
confidence: 99%